Diagnosis of the organizational culture of multicultural enterprises – introduction to in-depth research - Beata Domańska-Szaruga; Agnieszka Knap-Stefaniuk (Nowoczesne Systemy Zarządzania, 2022)
Based on the research carried out, the article presents the results of the diagnosis of the organizational culture of selected multicultural enterprises from Poland, Spain and Portugal. The research carried out by the authors of this article is a pilot study, conducted as an introduction to more extensive and in-depth research in the field of human resource management in conditions of cultural differences. Research on the role and significance of organizational culture in a multicultural work environment was carried out, inter alia, using Cameron and Quinn's competing value model, which the authors also refer to in this publication. The article presents in a graphic form only partial results of the research carried out in 2022. In this publication, they concern the types of organizational cultures in the surveyed enterprises. The authors also indicated differences in organizational culture between Polish enterprises and Spanish and Portuguese enterprises.